IndianNation. - Sellers, Jason R. (Journal of American History, 2015)
A review of the website "IndianNation," featuring information regarding the estimated 237,000 Native Americans listed on the U.S. Census of 1900, created and maintained by the University of Georgia’s Center for Virtual History and Willson Center for Humanities and Arts, and available at http://indiannation.org, is presented.